Molecular evidence for conspecificity of two desert Liolaemus lizards (Iguania: Liolaemidae) - de Gamboa, Margarita Ruiz; Correa, Claudio; Marambio-Alfaro, Yery; Riveros-Riffo, Edvin; Ortiz, Juan Carlos (Zootaxa, 2018)
Liolaemus audituvelatus (Núñez & Yáñez 1983) and L. manueli (Núñez, Navarro, Garín, Pincheira-Donoso & Meriggio 2003) are endemic species of the Atacama Desert of northern Chile that belong to the montanus group. Both species are considered cryptic from each other and can only be distinguished by their distribution ranges and karyotypes. Originally, there was a wide separation zone between their known distribution ranges, but later collections reduced the gap from 430 km to only 150 km. In this study, we review the geographic information about both species and report new localities within the distribution gap, where species identification becomes difficult. We performed a molecular phylogenetic analysis and applied several species delimitation methods to reassess the taxonomic status of both nominal species and new intermediate populations. Our analyses support the placement of L. manueli in the synonymy of L. audituvelatus. We discuss the biogeographic and conservation implications of this new synonymy.